2009
DOI: 10.1186/1757-1626-2-6462
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic resection of giant lipoma mimicking colonic neoplasm initially presenting with massive haemorrhage: a case report

Abstract: Lipomas of the colon are benign tumors that rarely occur. Their size ranges from 2 mm to several cm. They are usually asymptomatic but occasionally they present with clinical manifestations depending on tumor size, localization and complications, which often lead to diagnostic difficulty. A 40-year-old man presented with massive rectal haemorrhage. During colonoscopy a giant polyp of over 50 mm in its bigger diameter, with a thick stalk of 2 cm, located in the transverse colon, was revealed. Endoscopic resecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…The size of colonic lipomas ranges between 2 mm and 30 cm and may mimic colonic malignancies ( 13 ). The present case revealed that large colonic lipomas and malignant tumors may be difficult to differentiate prior to resection if only endoscopic observations are used.…”
Section: Discussionmentioning
confidence: 99%
“…The size of colonic lipomas ranges between 2 mm and 30 cm and may mimic colonic malignancies ( 13 ). The present case revealed that large colonic lipomas and malignant tumors may be difficult to differentiate prior to resection if only endoscopic observations are used.…”
Section: Discussionmentioning
confidence: 99%
“…Colonoscopy may show CLs in the form of a yellow elastic submucosal mass, but sometimes hemorrhage, necrosis, and mucosal ulceration may be seen 15 . (15) Regarding treatment, the general agreement is that CLs <2.0cm in diameter are accessible for endoscopic management, while this is not recommended for lesions >2.0cm due to the risk of complications 16 . (16) For those patients taken for surgical treatment, formal colectomy and limited colon resection are considered as adequate treatment modality, particularly in those cases with a confirmed preoperative diagnosis 17 .…”
Section: B Amentioning
confidence: 99%
“…(15) Regarding treatment, the general agreement is that CLs <2.0cm in diameter are accessible for endoscopic management, while this is not recommended for lesions >2.0cm due to the risk of complications 16 . (16) For those patients taken for surgical treatment, formal colectomy and limited colon resection are considered as adequate treatment modality, particularly in those cases with a confirmed preoperative diagnosis 17 . (17) According to Jiang et al, surgical intervention is appropriate when the lipoma is >4 cm in size; has associated intussusception and the patient is symptomatic, or when the lesion cannot be resected endoscopically 18 .…”
Section: B Amentioning
confidence: 99%
“…Lipomas of the colon and rectum are rare GI neoplasms, though they are the second most common benign tumors after adenomatous polyps [1], and the commonest non-epithelial neoplasms. They comprise about 5% of all GI tract tumors [2], with an incidence ranging from 0.035% to 4.4% [3].…”
Section: Introductionmentioning
confidence: 99%
“…or laparoscopic methods [12]. However, endoscopic removal is preferable over surgical excision, provided the cases are selected carefully and the procedure performed by skilled endoscopists in centers of excellence [1].…”
Section: Introductionmentioning
confidence: 99%